Kota Tanggap Lingkungan Berlandaskan Nilai Moral Islam - Ersina, Sriany (Fakultas Adab dan Humaniora UIN Alauddin, 2014)
Various disasters that happened in urban area in Indonesia has led human behavior to organize their surroundings in which they live. Islam as the guidance and way of life for mankind has given the instructions how to keep their surroundings in order to create the harmony. The moral crisis following the bad attitudes toward invironment Â has caused those divergences. In this case, we need awareness to create the perceptive city as one of belief manifestations. Therefore, it can grow on in human life. This article tries to talk about the relations of construction which creates perceptive city and design the city which is based on Islamic norms.